2017
DOI: 10.1038/s41598-017-02147-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesporous 3C-SiC Hollow Fibers

Abstract: In the present work, for the first time, we reported the exploration of mesoporous 3C-SiC hollow fibers via single-spinneret electrospinning of polyureasilazane (PSN) and polyvinylpyrrolidone (PVP) solution followed by high-temperature pyrolysis treatment. The resultant products were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM) and N2 adsorption. The as-prepared hollow fibers with totally mesoporous walls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Thermal protection in harsh environments is of fundamental importance for human beings, and materials have been developed from hides, bark and leaves in ancient times to natural fibers which are obtainable from animal, vegetable, or mineral sources for centuries, and now to various synthetic fibers and fabrics. , Recent achievements on synthetic fibers provide more exciting opportunities toward better thermal protection and management. For example, hollow fibers, biomimetic porous fibers, , and ultrafine fibers have shown advantages in thermal insulation over natural fibers, whereas the demand for more efficient thermal insulation fibers is still growing fast. For such a purpose, the forthcoming fibers should be as porous as possible, with an ultralow mass density and large porosity.…”
mentioning
confidence: 99%
“…Thermal protection in harsh environments is of fundamental importance for human beings, and materials have been developed from hides, bark and leaves in ancient times to natural fibers which are obtainable from animal, vegetable, or mineral sources for centuries, and now to various synthetic fibers and fabrics. , Recent achievements on synthetic fibers provide more exciting opportunities toward better thermal protection and management. For example, hollow fibers, biomimetic porous fibers, , and ultrafine fibers have shown advantages in thermal insulation over natural fibers, whereas the demand for more efficient thermal insulation fibers is still growing fast. For such a purpose, the forthcoming fibers should be as porous as possible, with an ultralow mass density and large porosity.…”
mentioning
confidence: 99%
“…XRD characterisation of SiC was detected in Figure 1 c. Five prominent characteristics peaks were noted at the two theta of approximately 35.4, 40.05°, 60.12°, 71.9° and 75.8°, which can be ascribed to the (111), (200), (220), (311), and (222) crystal face of SiC phase and is highly in line with the results of JCPDS, No. 29–1129 [ 37 ]. The XRD results confirmed the high purity of the SiC nanoparticles used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Completely hollow supramolecular architectures, typically produced from silicon carbide or graphene, [89][90][91] have also been reported via the self-assembly of short fluoropeptides. Building upon their earlier work on αγα-tripeptides, Burade et al have reported fluorinated sugar amino acid derived α,γ-cyclic tetra-and hexapeptides that adopt symmetric flat oval-and triangular-ring shaped β-strands.…”
Section: Fibrillar Assembliesmentioning
confidence: 99%
“…Completely hollow supramolecular architectures, typically produced from silicon carbide or graphene, [ 89–91 ] have also been reported via the self‐assembly of short fluoropeptides. Building upon their earlier work on αγα‐ tripeptides, Burade et al .…”
Section: Fluoropeptide Nano‐ and Micro‐assembliesmentioning
confidence: 99%